Phytoliths and rice: from wet to dry and back again in the Neolithic Lower Yangtze. (October 2015) - Weisskopf, Alison; Qin, Ling; Ding, Jinglong; Ding, Pin; Sun, Guoping; Fuller, Dorian Q
Abstract: Abstract : The cultivation of rice has had a major impact on both societies and their environments in Asia, and in China in particular. Phytolith assemblages from three Neolithic sites in the Lower Yangtze valley reveal that in early rice fields the emphasis was on drainage to limit the amount of water and force the rice to produce seed. It was only in the later third millennium BC that the strategy changed and irrigated paddies came into use. The results demonstrate that plant remains, including weed assemblages, can reveal wetter or drier growing conditions, showing changes in rice cultivation from flooded and drained fields to large, intensively irrigated paddies.